A study of customer acceptance towards Streamyx products offered by Telekom Malaysia (TM) Berhad, Melaka / Nur Eirna Jamaluddin - Jamaluddin, Nur Eirna (2009)
The purpose of this research is to study customer acceptance towards Streamyx products offered by TM. The study was conducted among customers in Melaka especially who live in Ayer Keroh area. Technology Acceptance Model (TAM) is one of the most suitable models available to study this customer acceptance toward these Streamyx products. The main objective of this research is to examine whether there is significant relationship between independent variables (perceived usefulness, perceived ease of use, attitude, behavioral intention and actual use) toward customer acceptance toward Streamyx products in TM (Telekom Malaysia). Other than that, to identify the most influence factor that affects the acceptance of Streamyx products and the level of acceptance toward Streamyx products offered by TM (Telekom Malaysia) among customers in Melaka. The research is conducted by using sampling frame. 100 of respondents have been asked by using questionnaire in order to gain information and feedback to the company. The questionnaire will has a set of questions that is question about the customer acceptance towards Streamyx products provided by TM and also Technology Acceptance Model (TAM). The findings showed that most of the customers can accept the Streamyx products offered by TM (Telekom Malaysia) Berhad. Although the customers accept the Streamyx products, the company needs to improve and maintain the products quality and service after purchase if they want builds long-term relationship with their customers onwards.